(untitled) (Economic and Political Thought, 2018)
The following paper presents a possible new explanation for the European Union’s turbulent integration. By combining elements of game theory, neo-functionalist theory and its neo-realist account as well as devoting special attention to liberal intergovernmentalism it presents a method of thinking about the way in which European states function and calculate their behaviours in relation to integration efforts. Through that it attempts to build an initial framework for an alternative way of thinking about integration and disintegration of the European Union. Countries attempt to control one another through products of a centralised political process, imposing limitations on freedom of action of others: the more control, the less freedom of action and the more integration as a result. The same mechanism can be both responsible for tendencies of integration as well as disintegration, since countries that fail to increase their ability to control others see that as an asymmetrical gain for others, and tend to opt out from integration, or to disassociate themselves from the project altogether.